Critical Study of Implementation of Distance Education Policy During a Pandemic - Vince Tebay (Formosa Journal of Multidisciplinary Research, 2023)
The convergence of technology as a learning media requires educators and learners to overwhelm online learning technology. This study intended to analyze the exact constraints of online learning systems during a pandemic in the Faculty of Social and Political Sciences, Cenderawasih University. This sort of research was descriptive in a qualitative approach. Sources of data came from interviews, observations, and literature studies. Data analysis ran through the stages of reduction, presentation, and verification of data. The legality of the data was experimented using triangulation. The result showed that there were three core elements which had been excluded by the existence of new media during the Covid-19 pandemic. First, the disposition of companies was based on audiovisual technology to accumulate profits as like subscription system of the Zoom Application. Second, the fading of the actuality of lecturer-student synergies only exist in conventional (face-to-face) learning. Third, the inflammation of humanist education which is summarized by independent learning.